Seventeenth Meeting of the National Development Council - Planning Commission (Planning Commission, 1961)
Since the completion of the Draft Outline of the Third Five Year Plan in June 1960, the plans and resources of States have been discussed in considerable detail and State Governments are now engaged in presenting their plans with a view to securing the approval of State legislature, arranging for implementation, and drawing up the annual plans for 1961-62. The Planning Commission has also reviewed the proposals of Central Ministries and has recently made a fresh assessment of resources for the country as a whole. In the light of these studies, it is now possible to take an overall view regarding the outlays, allocations and other aspects of the Third Plan. In the nature of things, both the formulation of the Third Plan and the attempt to match resources with needs present great complexity than in the First or even in the Second Plan. Speaking broadly, the general approach in the Third Plan is to take a view of those programmes of development which are essential and have to be undertaken during the period of the Plan, both for speeding up development and meeting minimum social requirements. By speeding up industrial production and careful planning of the pattern of industrial growth as well as the rapid development of agriculture, the Plan seeks to build up the essential productive basis for accelerated development. In each phase, the successful completion of these tasks is the essential condition for the achievement of the economic no less than the social goals of development.
Summary Record Government of India Planning Commission